Globalizing Flexible Work in Universities: Socio-technical dilemmas in internationalizing education - Michael Singh (Athabasca University Press, 2005)
We engage with and respond to the debate raised by this theme issue of the International Review of Research in Open and Distance Learning with a particular question in mind: namely, as universities are using new labor displacing technologies to export degrees to meet the international demand for higher education, how is this influencing – negatively and positively – the workers involved? Contemporary transitions in political and economic globalization are being used to press universities into becoming ‘transnational businesses,’ seemingly driven by a primary concern for marketing educational commodities. The neo-liberal politics driving these currents in universities are increasing the multiple online and offline networks. These local/ global meshworks engage the labors of a small but growing percentage of the world’s population (Singh, 2002, pp. 217-230). Writing this paper at Jilin University in China, we find that many of our academic colleagues and students have limited access to a personal desktop computer, the Internet, and email. They must pay for timed access to their email accounts and for downloading attachments. They do not have access to high-speed data networks. A timer indicates how long it will take to open and send emails. Around us, construction workers are building massive facilities to house the burgeoning on-campus student population. Their offline education is being supplemented – but not replaced by ever-advancing online technologies.